2016
DOI: 10.1590/0102-3772e32ne212
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem de competências, desenvolvimento humano e educação superior

Abstract: RESUMO Tendo como fundamento a psicologia do desenvolvimento humano, apresenta-se, neste artigo, uma ampliação conceitual à compreensão de competência. Esse é um termo polissêmico, com multiplicidade de concepções epistemológicas, éticas e ideológicas que imprimem complexidade aos processos formativos, especialmente em relação à formação pessoal e profissional na educação superior. Defende-se a noção de competência ancorada na mobilização intencional de diversos recursos próprios ao desenvolvimento humano: pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
17

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 7 publications
0
11
0
17
Order By: Relevance
“…In individual responses by competence resources, the generated number of responses is equal to the number of participants of the research (six), which is distributed among the concepts named "developed", "undeveloped" (little developed) and "not developed" for each competence assessed by the respondent. TCC1 TCC2 TCC3 TCC4 TCC5 TCC6 TCC7 TCC8 TCC9 TCC10 TCC11 TCC12 TCC13 TSC1 TSC2 TSC3 TSC4 TSC5 TSC6 TSC7 TSC8 TSC9 The results indicated that the educators signalized the development of transversal competences, that is, those related to practical knowledge, to the interpersonal, ethical and esthetical resources and of minor development on technical competences to the formal initial formation, which is based on the development of theoretical and conceptual resources and technical and scientific resources to the profession (Marinho- Araujo & Almeida, 2017). This, probably, indicates that the lack of specific formation in the field of social education in Brazil may not guarantee safety as to a practice related to the contexts of not formal education, as indicated by the Brazilian studies by Calegare (2005); Caro and Guzzo (2004); Dadico (2003), Dadico and Souza (2010);Dias (2007), Galvão (2014); Galvão and Marinho-Araujo (2017) and Soares (2008).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…In individual responses by competence resources, the generated number of responses is equal to the number of participants of the research (six), which is distributed among the concepts named "developed", "undeveloped" (little developed) and "not developed" for each competence assessed by the respondent. TCC1 TCC2 TCC3 TCC4 TCC5 TCC6 TCC7 TCC8 TCC9 TCC10 TCC11 TCC12 TCC13 TSC1 TSC2 TSC3 TSC4 TSC5 TSC6 TSC7 TSC8 TSC9 The results indicated that the educators signalized the development of transversal competences, that is, those related to practical knowledge, to the interpersonal, ethical and esthetical resources and of minor development on technical competences to the formal initial formation, which is based on the development of theoretical and conceptual resources and technical and scientific resources to the profession (Marinho- Araujo & Almeida, 2017). This, probably, indicates that the lack of specific formation in the field of social education in Brazil may not guarantee safety as to a practice related to the contexts of not formal education, as indicated by the Brazilian studies by Calegare (2005); Caro and Guzzo (2004); Dadico (2003), Dadico and Souza (2010);Dias (2007), Galvão (2014); Galvão and Marinho-Araujo (2017) and Soares (2008).…”
Section: Resultsmentioning
confidence: 97%
“…The theoretical reflections of School Psychology and the notion on competences proposed by Araujo (2003) and Marinho-Araujo and Almeida (2017) discussed in this manuscript, added to the results from the current study, were aimed to expand the conceptions, which form the propositions of initial and continuous formation of the workers from social education. The work characteristics of social educator in the contemporary scenario of non-formal educative institutions are relevant for the actuation and intervention from School Psychology, specially committed to the adult development in contemporary contexts of educational practices.…”
Section: Final Considerationsmentioning
confidence: 96%
See 3 more Smart Citations